(untitled) (Research, Society and Development, 2022)
The figure of the Psychologist becomes indispensable in confronting COVID-19, as the pandemic ends up bringing with it numerous factors that can favor changes in the mental health condition for various audiences, such as the case of the elderly. The objective was to understand the role of the Psychologist in the mental health of the elderly during the COVID-19 pandemic period. Methodologically, this is a literature review, with a descriptive and exploratory approach, in the databases of Latin American and Caribbean Literature in Health Sciences (LILACS) and in the Scientific Electronic Library Online (SciELO). The bibliographic review contemplated three points specifically, among them: the overview of COVID-19; the mental health of the elderly; and, the role of the psychologist regarding the mental health of the elderly in the pandemic. It is concluded that the figure of the psychologist is essential in the mental health care of the elderly in this pandemic period, as these professionals tend to minimize the feelings of anguish and fear experienced by the elderly. Note that this service, despite taking place at a distance, becomes necessary for those who need to take care of their mental health, especially in such a unique period as this one. However, the need to develop more research focused on this area is perceived.